Predictive algorithms and criminal justice: expectations, challenges and a particular view of the Spanish VioGén system - Pilar Martín Ríos (Rivista Italiana di Informatica e Diritto)
The irruption in the field of the Administration of Justice of instruments linked to Artificial Intelligence and to the algorithms on which it is frequently based, is a well-known reality. In addressing this issue, some problems will inevitably need to be resolved, relating to access to justice, transparency or the impact of the digital divide. In this study, we will focus on the examination of AI in the Administration of Justice in general and, specifically, on its influence on criminal proceedings. Within this framework, we will also examine the emergence of the use of systems that, while employing algorithms, do not meet the criteria that allow them to be classified as AI. We will focus on the Spanish case, using the VioGén system as a paradigmatic example, although it is unavoidable to refer to the overall situation, given the global dimension of the analyzed phenomenon.